Studying the Role of Heme Oxygenase-1 in Obese Patients - Nabaa Adnan Mohammed; Fayhaa M. Khaleel (مجلة بغداد للعلوم, 2024)
Heme oxygenase-1(HO-1) is an enzyme that catalyzes and breaks down heme molecules into biliverdin, free iron, bilirubin, and carbon monoxide. This study aims to investigate the levels and role of (HO-1) in obese patients against oxidative stress and its relationship to obesity. The study included 139 samples: (84 obese and 55 non-obese persons). Both study groups were divided into four groups based on their Body Mass Index (BMI). Blood sample was collected from obese persons and control groups (men and women) at AL-Yarmouk Hospital and the National Diabetes Research Center at the period between December-2022 until June-2023. Some biochemical parameters were measured for all studied groups, which include: Determining of HO-1 levels in serum by using the ELISA-technique, lipid profile and fasting serum glucose (FSG) assessed enzymatic. BMI levels were found to be increased significantly in obesity class II group, obesity-class I group, and overweight group compared with normal weight groups. Also, the results showed that waist hip ratio (WHR (was significantly increased (p≤ 0.05) in groups obesity class II, obesity class I, and overweight group compared with normal weight group. Also, the results showed that the HO-1 levels were higher in obese-class I patients and obese-class II group compared with normal-weight and overweight groups. The statistical analysis displayed that, the level of HO-1 is associated negatively with BMI in normal weight group (G1), while positively with the obesity-class II, obesity-class I, and overweight groups. We conclude from this study that the body's first line of defense against oxidative stress attack is HO-1. This cell-protective enzyme reduces oxidative stress and is vital for controlling lipogenesis, which is crucial for the development of metabolic diseases and its complications.